Effect of Inulin on the Formation Kinetics of Methane Hydrate - Yaqub, S. (Springer Science and Business Media Deutschland GmbH, 2021)
In the petroleum industry, clathrate formation during natural gas transportation is the dominant flow assurance problem. The use of kinetic hydrate inhibitor (KHI) is one of the optimum approaches to inhibit hydrate formation and provide flow assurance in offshore gas pipelines. Therefore, the performance of inulin on the formation kinetics of methane (CH4) clathrate is examined. At 274Â K and 7.5Â MPa aÂ sapphire hydrate reactor is used to perform kinetic experiments. Gas hydrate kinetics dealt with fundamental knowledge about hydrate onset time, the initial formation rate, and the amount of gas consumed at numerous concentrations (0.12, 0.5, and 1wt ) of biopolymer. Results reveal that the addition of inulin forms substantial hydrogen bonding with water (H2O) molecules and efficiently inhibits the CH4 hydrate formation for 37Â min. The increased biopolymer concentration to 1wt showed increasing KHI performance. In addition, the hydrate formation rate is reduced by 51 better than H2O. While by adding small amounts of inulin, gas consumption is also significantly (65) decreased. It is concluded that inulin can be an imminent choice for inhibiting CH4 hydrate formation in offshore gas pipelines. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.